Embedded fiber sensors to monitor temperature and strain of polymeric parts fabricated by additive manufacturing and reinforced with NiTi wires - Nascimento, Micael (2020)
POCI-01-0145-FEDER-016414 (FIBR3D) BI/UI96/6642/2018 BI/UI96/6643/2018 PD/BD/128265/2016 UID/CTM/50025/2019 UIDB/00667/2020 FCT-SFRH/BD/146885/2019 UIDB/50025/2020 UIDP/50025/2020